Hemodynamic responses to simulated weightlessness of 24-h head-down bed rest and KAATSU blood flow restriction - Nakajima, Toshiaki; Iida, Haruko; Kurano, Miwa; Takano, Haruhito; Morita, Toshihiro; Meguro, Kentaro; Sato, Yoshiaki; Yamazaki, Yoshihisa; Kawashima, Sino; Ohshima, Hiroshi; Tachibana, Shouichi; Ishii, Naokata; et al. (European journal of applied physiology, 2008)
The KAATSU training is a unique method of muscle training with restricting venous blood flow, which might be applied to prevent muscle atrophy during space flight, but the effects of KAATSU in microgravity remain unknown. We investigated the hemodynamic responses to KAATSU during actually simulated weightlessness (6° head-down tilt for 24 h, n = 8), and compared those to KAATSU in the seated position before bed rest. KAATSU was applied to the proximal ends of both the thighs. In the seated position before bed rest, sequential incrementing of KAATSU cuff pressure and altering the level of blood flow restriction resulted in a decrease in stroke volume (SV) with an increase in heart rate (HR). KAATSU (150–200 mmHg) decreased SV comparable to standing. Following 24-h bed rest, body mass, blood volume (BV), plasma volume (PV), and diameter of the inferior vena cava (IVC) were significantly reduced. Norepinephrine (NOR), vasopressin (ADH), and plasma renin activity (PRA) tend to be reduced. A decrease in SV and CO induced by KAATSU during the simulated weightlessness was larger than that in the seated position before bed rest, and one of eight subjects developed presyncope due to hypotension during 100 mmHg KAATSU. High-frequency power (HF RR ) decreased during KAATSU and standing, while low-frequency/high-frequency power (LF RR /HF RR ) increased significantly. NOR, ADH and PRA also increased during KAATSU. These results indicate that KAATSU blood flow restriction reproduces the effects of standing on HR, SV, NOR, ADH, PRA, etc., thus stimulating a gravity-like stress during simulated weightlessness. However, syncope due to lower extremity blood pooling and subsequent reduction of venous return may be induced during KAATSU in microgravity as reported in cases of lower-body negative pressure.